KODE ETIK WISATAWAN DALAM MENUNJANG KELESTARIAN GUNUNG API PURBA NGLANGGERAN - Eryd Saputra (Universitas Merdeka Malang, 2017)
Abstract Nglanggeran ancient volcano is the main tourist attraction in Gunungkidul regency, which the number of the visitor is quite high. Guidance need to organize the manner of the tourist. In order to maintain the ancient volcano preservation on the future. Tourist code of conduct is one of the tourist attraction environment. The purposes of this reseach was to analyze of the strategy, which have done by the eco-tourism administrator area of the nglanggeran ancient volcano, in applying of the tourist codes of conduct towards tourist behavior. This reseach was conducted through qualitative descriptive method, along with participant observation, interview, and documentation as data for instruments collection. The result of this research was the ecotourism administrator area which has already applayed the tourism codes of conduct to the tourist and impact on the changes of the tourist attitude to pay more attention to the environment.